Using Transcript Based Lesson Analysis to analyze students’ scientific Literacy About Lithium-Ion Batteries on the Concept of Redox Reaction - Rira Octa Ningsi*; Asep Supriatna; Hernani Hernani (Universitas Syiah Kuala, 2023)
The lithium-ion battery context can be implemented in learning by using green chemistry in analyzing students' scientific literacy. This study aims to investigate the scientific literacy profile of students who appear in lithium-ion battery learning with a problem-based learning model in high school. The scientific literacy indicator is used based on the 2015 PISA Framework. The method used in this research is descriptive qualitative. This research was conducted in one of the high schools in the city of Bogor, West Java. The research subjects consisted of 27 students of class XII MIPA 6. The instruments used were observation, LKPD, and audio-video during the learning process. The data obtained were analyzed using Transcript-Based Lesson Analysis (TBLA). The results showed that the 4 indicators of scientific literacy appeared in the learning of the first meeting and the second meeting. The results show that the profile of the emergence of scientific literacy of students at the first meeting is an indicator of scientific knowledge (39%); indicators of science competence (38%); context indicators (13%); and science attitude indicators (10%). The profile of the emergence of scientific literacy of students at the second meeting, namely the knowledge indicator (37%); competency indicators (31%); context indicator (25%); and science attitude indicators (7%). The overall results show that the 4 indicators of scientific literacy that appear are related to each other, but are still low. The low achievement of students' scientific literacy is because they are not used to expressing what is in their minds and teachers have not been able to ask questions that encourage them to be scientifically literate. Analysis of scientific literacy activities and dialogue during learning can be used as a reflection for teachers to evaluate and improve further learning.